The characterization of a novel S100A1 binding site in the N-terminus of TRPM1. (September 2016) - Jirku, Michaela; Lansky, Zdenek; Bednarova, Lucie; Sulc, Miroslav; Monincova, Lenka; Majer, Pavel; Vyklicky, Ladislav; Vondrasek, Jiri; Teisinger, Jan; Bousova, Kristyna
Graphical abstract: Highlights: ⿢ TRPM1 N-terminus binds calcium binding protein S100A1. ⿢ Formation of TRPM1/S100A1 complex is facilitated through interactions of clusters positively charged (K271A, R273A, R274A) and hydrophobic (L263A, V270A, L276A) residues. ⿢ TRPM1 N-terminal domain distinctly does not change the secondary structure content upon S100A1 binding. ⿢ Molecular model describes potential molecular mechanism of TRPM1/S100A1 complex formation. Abstract: Transient receptor potential melastatin-1 channel (TRPM1) is an important mediator of calcium influx into the cell that is expressed in melanoma and ON-bipolar cells. Similar to other members of the TRP channel family, the intracellular N- and C- terminal domains of TRPM1 are expected to play important roles in the modulation of TRPM1 receptor function. Among the most commonly occurring modulators of TRP channels are the cytoplasmically expressed calcium binding proteins calmodulin and S100 calcium-binding protein A1 (S100A1), but the interaction of TRPM1 with S100A1 has not been described yet. Here, using a combination of biophysical and bioinformatics methods, we have determined that the N-terminal L242-E344 region of TRPM1 is a S100A1 binding domain. We show that formation of the TRPM1/S100A1 complex is calcium-dependent. Moreover, our structural model of the complex explained data obtained from fluorescence spectroscopy measurements revealing that the complex formation is facilitated through interactions of clusters positively charged (K271A, R273A, R274A) and hydrophobic (L263A, V270A, L276A) residues at the N-terminus of TRPM1. Taken together, our data suggest a molecular mechanism for the potential regulation of TRPM1 by S100A1.